Penyuluhan Pengisian dan Pelaporan SPT PPh Tahunan Wajib Pajak Orang Pribadi Bagi Guru SMP IT Daarul Istiqlal Marindal-I - Jayusman, Sri Fitria; Munawaroh, Munawaroh; Hasibuan, Melisa Zuriani; Munawaroh, Wilda Sri; Harahap, Rasyid Yudha (Yayasan Rahmat Islamiyah, 2024)
Based on the PKM team survey, the problem at SMP IT Daarul Istiqlal Marindal I is that teachers' knowledge and understanding of taxation is still low. The problem continued when an interview with one of the teachers named